2005
DOI: 10.1103/physrevb.71.104418
|View full text |Cite
|
Sign up to set email alerts
|

Half-ordered state in the anisotropic Haldane-gap antiferromagnetNi(C5D14N2)2

Abstract: Neutron diffraction experiments performed on the Haldane gap material Ni(C5D14N2)2N3(PF6)in high magnetic fields applied at an angle to the principal anisotropy axes reveal two consecutive fieldinduced phase transitions. The low-field phase is the gapped Haldane state, while at high fields the system exhibits 3-dimensional long-range Néel order. In a peculiar phase found at intermediate fields only half of all the spin chains participate in the long-range ordering, while the other half remains disordered and g… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 19 publications
1
13
0
Order By: Relevance
“…35 This independent behavior of the two kinds of chains is very interesting because the signals around the a axis were observed in the LRO phase at 1.5 K, which means that cooperative behavior is expected.…”
Section: A Spin Excitations Near H C Regionmentioning
confidence: 92%
See 1 more Smart Citation
“…35 This independent behavior of the two kinds of chains is very interesting because the signals around the a axis were observed in the LRO phase at 1.5 K, which means that cooperative behavior is expected.…”
Section: A Spin Excitations Near H C Regionmentioning
confidence: 92%
“…From the neutron-scattering experiments, it was reported that the two types of chains in NDMAP behave independently against the external magnetic field. 35 In addition, Ref. 33 showed an interesting H − i ͑i =1,2͒ phase diagram of the sublattice magnetization at zero temperature, where the i stands for the angle between the external magnetic field and one of the principal axes of Ni-O 6 octahedron in the two types of chains.…”
Section: A Spin Excitations Near H C Regionmentioning
confidence: 98%
“…In addition, we have discussed the possibility to observe the novel consecutive field-induced phase transitions in NDMAP. Although the observation of this peculiar phenomenon has been initiated, 8) it is need further investigations to reveal the detailed structure of the order and other critical behavior both from experimental and from theoretical sides.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, in NDMAP we may observe the different critical behavior just by increasing the field. It is worth mentioning that recently a trace of such behavior has been observed by the neutron elastic scattering 8) although a detailed investigation of the critical behavior has not been performed yet. §3.…”
mentioning
confidence: 99%
“…Note that the anisotropies, d and e, make the x-axis easy while the z-axis hard. Considering that the anisotropy z-axis in NDMAP is tilted in the crystallographic a2c plane [6], we assume h has the x and the z components: h ¼ hðsin y; 0; cos yÞ.…”
Section: Introductionmentioning
confidence: 99%